2021
DOI: 10.1021/acs.orglett.1c01580
|View full text |Cite
|
Sign up to set email alerts
|

Copper(II) Acetate-Induced Oxidation of Hydrazones to Diazo Compounds under Flow Conditions Followed by Dirhodium-Catalyzed Enantioselective Cyclopropanation Reactions

Abstract: A tandem system comprising in-line diazo compound synthesis and downstream consumption in a rhodium-catalyzed cyclopropanation reaction has been developed. Passing hydrazone through a silica column absorbed with Cu­(OAc)2-H2O/N,N-dimethylaminopyridine oxidized the hydrazone to generate an aryldiazoacetate in flow. The crude aryldiazoacetate elutes from this column directly into a downstream cyclopropanation reaction, catalyzed by the chiral dirhodium tetracarboxylates, Rh2(R-p-Ph-TPCP)4 and Rh2(R-PTAD)4. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…33 During recent studies to optimize some specific rhodium-catalyzed cyclopropanation, we discovered that HFIP (10 equiv) desensitizes the reaction to water and N,N′-dimethylaminopyridine (DMAP). 7,34 Given this exciting and unexpected result, we suspected that we could leverage this effect to deactivate a wide range of other nucleophilic poisons and reactive functionality that typically interfere with the cyclopropanation reaction. 19,30,31 HFIP can hydrogen bond with, or even formally protonate, different nucleophiles due to its relatively high acidity, preventing them from coordinating with the dirhodium catalyst and the rhodium carbene intermediate.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 During recent studies to optimize some specific rhodium-catalyzed cyclopropanation, we discovered that HFIP (10 equiv) desensitizes the reaction to water and N,N′-dimethylaminopyridine (DMAP). 7,34 Given this exciting and unexpected result, we suspected that we could leverage this effect to deactivate a wide range of other nucleophilic poisons and reactive functionality that typically interfere with the cyclopropanation reaction. 19,30,31 HFIP can hydrogen bond with, or even formally protonate, different nucleophiles due to its relatively high acidity, preventing them from coordinating with the dirhodium catalyst and the rhodium carbene intermediate.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…41−45 In this study, good reactivity was generally observed with oxygen nucleophiles at low levels of HFIP (Table 3b). Substrates including acetone (32), nitromethane (33), and phenylisocyanate (34) were all tolerated without the use of HFIP. However, more nucleophilic compounds, like N,N′-dimethylformamide (DMF, 39) required 10 equiv HFIP to ensure compatibility.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Other notable advances in Cu-catalyzed reactions include the following publications: (1) Cu-catalyzed diazidation reactions; (2) Diastereo-and enantioselective oxidative 1,6-conjugate addition; (3) C–H amination of 8-aminoquinoline-directed ferrocenes; (4) Cu-catalyzed hydroxymethylation of alkynes with formic acid; (5) Cu-catalyzed synthesis of indolyl benzo­[ b ]­carbazoles; (6) Cu-catalyzed tandem cross-coupling and alkynylogous aldol reaction to access exocyclic α-allenols; (7) Tandem Cu- and Rh-catalysis for oxidation of hydrazones and enantioselective cyclopropanation; (8) Cu-catalyzed CF 2 H-substituted 2-amidofurans; (9) Cu-catalyzed annulation of indolyl α-diazocarbonyl to access carbazoles; (10) Cu-catalyzed enantioselective 1,2-reduction of cycloalkenones; (11) Cu-catalyzed enantiodivergent alkynylation of isatins; (12) Cu-catalyzed β-lactam formation from oximes and methyl propiolate; (13) Cu-catalyzed aminosulfonylation of O -homoallyl benzimidates; (14) Cu-catalyzed multicomponent trifluoromethyl­phosphorothiolation of alkenes; (15) Cu-catalyzed chloro-arylsulfonylation of styrene derivatives; (16) Cu-catalyzed synthesis of 5-carboxyl-4-perfluoroalkyl triazoles; (17) Cross-nucleophile coupling of β-allenyl silanes with tertiary C–H bonds to access 1,3-dienes; (18) Cu-catalyzed C­( sp 3 )–H functionalization of O -pentafluorobenzoyl ketone oximes; (19) Total regioselectivity of hydrobromination of alkenes controlled by Fe or Cu catalyst; (20) Enantioselective synthesis of trifluoromethyl cyclopropylboronates by Cu catalysis; (21) Cu-catalyzed asymmetric cyclization of alkenyl diynes; (22) Synergistic Ir/Cu catalysis for asymmetric allylic alkylation of oxindoles; (23) Hydrosilylation of alkynes and alkenes with Cu-photocatalysis under continuous flow conditions; (24) Cu-based water oxidation catalysts with consecutive ligand-based electron transfer; (25) Heteroleptic copper-based complexes for energy-transfer processes: E → Z isomerization and tandem photocatalytic sequences; (26) Copper-catalyzed aminoheteroarylation of unactivated alkenes through distal heteroaryl migration; (27) Copper-catalyzed syntheses of multiple functionalized allenes via three-component reaction of enynes; (28) Unified mechanistic concept of the copper-catalyzed and amide-oxazoline-directed C­(sp 2 )–H bond functionalization; (29) Cu-catalyzed C–H allylation of benzimidazoles with allenes; (30) Synthesis of 1,2-aminoalcohols through enantioselective aminoallylation of ketones by Cu-catalyzed reductive coupling; (31) Copper-catalyzed N-directed distal C­(sp 3 )–H sulfonylation and thiolation with sulfinate salts; and (32) Dehydrogenative aza-[4 + 2] cycloaddition of amines with 1,3-dienes via dual catalysis …”
Section: Recent Reports On Cu-catalyzed Reactionsmentioning
confidence: 99%
“…Recently, the Davies and Stahl groups developed a batch methodology using copper­(II) acetate hydrate [Cu­(OAc) 2 –H 2 O] as a precatalyst under aerobic conditions to oxidize a wide scope of hydrazone compounds to the corresponding aryldiazoacetate in high yields . Building upon this work, we have investigated the application of these reaction conditions to two flow processes: a simple benchtop setup suitable for laboratory applications and a potentially industrially relevant process described herein. In the present study, we seek to develop a continuous process consisting of a three-phase flow system to accommodate the aerobic hydrazone oxidation with immediate consumption of the aryldiazoacetate in a downstream, semibatch reaction.…”
Section: Introductionmentioning
confidence: 99%